NITROPHOSPHORIC FERTILIZERS BASED ON A MOLTEN AMMONIUM NITRATE WITH THE ADDITION OF TRISODIUM PHOSPHATE WASTE - Khoshimkhanova , Muhayyo; Dehkanov , Zulfikahar; Sharapova , Durdona (Digital technologies in industry, 2025)
This scientific study looks at the make-up, how they are made, and the agrochemical properties of nitrogen-phosphorus fertilizers made from ammonium nitrate (saltpeter) and trisodium phosphate waste. The study found the right amounts of ammonium nitrate and trisodium phosphate waste to use as a source of phosphorus and studied the physical and chemical properties of the mix. The efficacy of these fertilizers is evaluated based on their impact on plant growth and soil fertility. The findings demonstrated that this fertilizer type serves as an excellent supply of nitrogen and phosphate for crops, promoting environmental sustainability via waste recycling. We have proposed modifications to the manufacturing process to enhance its economic efficiency. We noted that reducing the explosive risk of ammonium nitrate and incorporating trisodium phosphate waste yields a complex fertilizer including nitrogen and phosphorus. We looked into how to make effective nitrogen-phosphorus fertilizers with complex compositions by mixing waste trisodium phosphate into a solution of ammonium nitrate. We assess the physico-chemical characteristics (grain consistency) of the resultant goods.